Pengaruh Lompat Tali (Rope Jump) Terhadap Kelincahan Pada Anak Usia 9-10 Tahun Di Sdn Losari 153 Surakarta - Amaliyah, Fathiyah Khairul, Agus Widodo, S.Fis, M.Kes (2017)
Background: In children aged 9-10 years entered the stage of motor development. One element of the motor development component is agility. Agility is one of the components required for all activities that require the speed of change in position of the body and its parts. In this case agility can be enhanced by administering the provision of jump rope exercises (jump rope). Objective: To investigate the effect of jump rope (jump rope) against agility in children aged 9-10 years in SDN Losari 153 Surakarta. Method: This research used was quasi-experimental (quasi-experimental) by using a non equivalent control group. Intake of respondents using purposive sampling method with insklusi and exclusion criteria. Respondents of this study as many as 22 people were divided into two groups. Results: Data were obtained after calculating by SPSS that is normally distributed. Statistical tests were used to test the effect of which is paired samples t-test p value obtained (0,000) <0.05. And different statistical tests to test the effect of using independent t-test showed the p value (0.006) <0.05. Conclusion: Based on these data we can conclude that there is the effect of jump rope exercises (jump rope) against agility in children aged 9-10 years in SDN Losari 153 Surakarta. Keywords: Jump rope, Agility, Children.